Isolation of E. coli phages from environmental water samples and analysis of their effect on periodic epidemics of cholera - Sultana, Navila (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.